2020
DOI: 10.1016/j.jbo.2020.100310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of grafted cartilage in osteoarticular frozen autografts for reconstruction after resection of malignant bone and soft-tissue tumor involving an epiphysis

Abstract: Highlights Frozen autograft of tumour-bearing bone using liquid nitrogen as a recycling autograft has various advantages. This paper is the first report focusing on the fate of grafted cartilage in recycled autograft after bone tumour excision. We found hemicondylar frozen autograft is promising reconstruction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The rate of postoperative osteoarthritic change after reconstruction of osteoarticular allograft, or osteoarticular frozen autograft including total epiphysis, were reported to be 39–100% in the previous studies 15 , 31 , 47 . In our study, osteoarthritic change was observed in 5 of the 10 (50%) AYA patients who had underwent osteoarticular frozen autograft reconstruction, while 4 of the 5 pediatric patients (80%) and 0 of the 2 older adult patients (0%) developed osteoarthritic changes after osteoarticular frozen autograft reconstruction (Table 2 ).…”
Section: Discussionmentioning
confidence: 94%
“…The rate of postoperative osteoarthritic change after reconstruction of osteoarticular allograft, or osteoarticular frozen autograft including total epiphysis, were reported to be 39–100% in the previous studies 15 , 31 , 47 . In our study, osteoarthritic change was observed in 5 of the 10 (50%) AYA patients who had underwent osteoarticular frozen autograft reconstruction, while 4 of the 5 pediatric patients (80%) and 0 of the 2 older adult patients (0%) developed osteoarthritic changes after osteoarticular frozen autograft reconstruction (Table 2 ).…”
Section: Discussionmentioning
confidence: 94%
“…A study on frozen autografts after resection of malignant bone tumors (mostly osteosarcomas) with epiphyseal involvement compared 27 patients with a mean age of 31.6 years (range 12-72 years) and a mean follow-up period of 94.0 months (range 6-217 months). They found that only 1 of 23 patients in the total epiphyseal freezing group remained osteoarticular graft survived until the final follow-up (19). The other 22 patients had developed osteoarthritic changes by the final follow-up (19).…”
Section: Discussionmentioning
confidence: 99%
“…They found that only 1 of 23 patients in the total epiphyseal freezing group remained osteoarticular graft survived until the final follow-up (19). The other 22 patients had developed osteoarthritic changes by the final follow-up (19). Meanwhile, all four of the patients who underwent intraepiphyseal resection for partial preservation of the healthy cartilage had excellent osteoarticular graft survival (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that joint cartilage is irradiated to a suppressive dose makes chondrolysis and secondary arthritic changes theoretically inevitable. Cartilage aggression and eventually destruction has also been observed in other methods of “sterilizing” bone autografts from tumoral cells, like immersion in liquid nitrogen and autoclaving as described by Hayashi et al [ 38 ] Moreover, in case of nonanatomic reduction and fixation of the reimplanted graft, secondary osteoarthritis may develop earlier, and the risk of secondary hip replacement in an acetabulum with a nonunion may impair final results. In fact, the patient of the second case reported, developed osteoarthritic changes while the younger patient of the first reported case did not present any such changes during follow-up.…”
Section: Discussionmentioning
confidence: 99%